Exploring the Perceived Affordable Residential Condominium among Middle-Income Cambodian People in Phnom Penh, Cambodia - Chamnab Voeun; Sarom Mok; Bora Khath (Universitas Majalengka, 2026)
Ongoing economic difficulties, such as stricter credit requirements and low domestic spending, have made the residential real estate market’s steady decline worse in Cambodia. In light of this, the fundamental purpose of this study was to determine how middle-income individuals who wish to live in Phnom Penh in the future will be affected by the city’s overgrowth in real estate and housing prices, as well as how to make condominiums in the Phnom Penh area accessible through both condominium design and policies. Through the analysis of secondary data and expert interviews at real estate firms, this study employed qualitative approaches. The results showed that although middle-income earnings increased, they did not rise in tandem with the Phnom Penh area’s rapidly increasing real estate values. Cambodian middle-income people might eventually be unable to buy condominiums in the Phnom Penh area as a result of this. Additionally, middle-class people find it increasingly difficult to locate reasonably priced condominiums in the Phnom Penh area because developers are discouraged from investing in these kinds of developments due to their inability to make a profit. This study has looked at strategies to help developers provide more reasonably priced condominiums and to make it easier for middle-class people to purchase condominiums in the Bangkok area through a number of support programs. The results showed that the home loan policy, tax reduction, bonus, and construction material cost reduction were among the collection of supportive policies that might be used.